2009
DOI: 10.1038/jhg.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

No association between the brain-derived neurotrophic factor gene and panic disorder in Japanese population

Abstract: Panic disorder (PD) is a severe and chronic psychiatric disorder, with significant genetic components in the etiology. Brain-derived neurotrophic factor (BDNF) gene, which has regulatory effects on neurotransmitter systems such as serotonin and dopamine, is a candidate for susceptibility locus of PD. This study investigated three single-nucleotide polymorphisms (SNPs) of BDNF (rs6265 (Val66Met), rs11030104 and rs7103411) in Japanese patients with PD and controls. No significant association was observed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Database search identified six studies that met the inclusion criteria (Lam et al ., ; Shimizu et al ., ; Lim et al ., ; Ishii et al ., ; Otowa et al ., ; Han et al ., ). In summary, a total of 20 potentially relevant articles were found after searching the PubMed and Embase databases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Database search identified six studies that met the inclusion criteria (Lam et al ., ; Shimizu et al ., ; Lim et al ., ; Ishii et al ., ; Otowa et al ., ; Han et al ., ). In summary, a total of 20 potentially relevant articles were found after searching the PubMed and Embase databases.…”
Section: Resultsmentioning
confidence: 99%
“…() reported a significant association between Met/Met polymorphism and PD risk. Other previous case–control studies, however, reported no association between PD risk and the Val66Met polymorphism (Lam et al ., ; Shimizu et al ., ; Lim et al ., ; Otowa et al ., ; Konishi et al ., ; Konishi et al ., ; Han et al ., ). This meta‐analysis included 1,230 patients and 1,612 control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, given several association studies (n = 103-1241), there is also insufficient evidence to suggest that panic disorder, an anxiety disorder characterized by disabling and recurrent panic attacks, is associated with the Val66Met polymorphism. [81][82][83][84] Meta-analyses have also generally failed to report significant associations between Val66Met genotype or allelotype and anxiety disorders. 71 Ultimately, it may be the case that the Val66Met polymorphism only provides susceptibility to trait anxiety that is independent of a psychiatric diagnosis, with the aforementioned anxiety disorders presumably maintaining otherwise distinct etiologies.…”
Section: Human Neuroscience Of the Val66met Polymorphismmentioning
confidence: 93%
“…No association of BDNF Val 66 Met polymorphism has been found with anxiety disorders including generalized anxiety disorder (Surtees et al, 2007), panic disorder (Lam et al, 2004;Otowa et al, 2009;Shimizu et al, 2005) and post-traumatic stress disorder except in one community sample of children and adolescents (Tocchetto et al, 2011).…”
Section: Introductionmentioning
confidence: 96%